Ijmaʿ on the Prohibition of Bank Interest: A Critical Analysis of Yusuf Al-Qaradawi’s View (1926–2022) - Aziz, Jamal Abdul; Rohmah, Umdah Aulia; Al-Qarni, Royyan Quwais; Pamuji, Rino Agus; Yanuar, Faiz (Universitas Islam Negeri Alauddin Makassar, 2026)
Throughout Islamic history, the prohibition of interest has faced diverging opinions with sharp disagreements between those who forbid and allow it. Despite this, Yusuf al-Qaradawi (1926-2022), a prominent contemporary scholar, views the prohibition of bank interest as ijma (consensus) that is indisputable. This view appears unusual given the strict theoretical requirements in usuliyyah to claim ijma. This article traces al-Qaradawi's argumentation regarding the consensus on bank interest and analyzes it using the usul fiqh theory of ijma. This is qualitative research relying on literature, specifically al-Qaradawi's works, analyzed via triangulation, namely the use of deductive and inductive methods in a proportional manner. The study finds that al-Qaradawi’s claim rests on agreements by international Islamic bodies, including Al-Azhar (1965), the Fiqh Academy of Makkah (1985), and the OIC Fiqh Academy in Jeddah (1986). However, when analyzed through ijma theory, this claim fails to meet essential elements, specifically the requirement for unanimous agreement among all mujtahids globally without exception. The conference attendees did not fully represent all mujtahids worldwide, making total consensus impossible. Consequently, the argument lacks the binding force of ijma and remains a non-binding ijtihad or fatwa. In general, it can be affirmed that the laws of ijmak in fiqh are essentially only claims, because the evidence of the achievement of ijmak as stipulated in the fiqh proposal can never really be shown.